Reaching women at work with health programming in Bangladesh: results of difference-in-differences analysis among female factory workers. Issue 1 (1st January 2021) - Chace Dwyer, Sara; Hossain, Md Irfan; Bajracharya, Ashish; Jain, Aparna
Abstract: The rapid growth of Bangladesh's ready-made garment sector has transformed the country's economy while also employing a predominantly female workforce. Companies have begun collaborating with NGOs to provide health messages to and expand health services for workers. This study evaluates the effect of the Health Enables Return (HER) health model's approach of using peer health educators to deliver health messages and increased availability of health products. Using repeated cross-sectional data from female workers in HERhealth and comparison factories between May 2015 and March 2017, baseline ( n  =   1704) and endline ( n  = 1503) samples were matched on eight characteristics and then difference-in-differences estimations were used to determine the effect of the HERhealth model on knowledge and behaviours. The average changes over time in knowledge and behaviours were statistically different between the HERhealth and comparison factories. Knowledge of when a woman is at higher risk for pregnancy during her menstrual cycle increased from baseline to endline in both groups but was 12 percentage points greater in the HERhealth factories than in the comparison. An increase in family planning use among ever-married women was observed in the HERhealth factories but decreased in the comparison factories leading to a 12 percentage point difference-in-differences. The greatest effect of the HERhealth model was observed on women's use of sanitary products for menstrual management which significantly increased in both groups, but the increase was 35% greater in the HERhealth factories. The HERhealth model is effective in increasing knowledge and in improving health behaviours when health products are available in factory infirmaries.